INDEX RTSN – REGIONAL TRANSPORT SERVICE NEEDS (Perner's Contacts, 2010)
Regional Transport Service is a widely discussed issue. The complexity of factorsinfluencing Transport Services is comparatively wide, given by the high amount offactors and their different impact on the level of Transport Services. The factors aredivided into two groups. One with short term invariability the other with short termvariability. Index RTSN expresses the short term invariable factor of ResidentialStructure and Urbanization. The methodology of determining the RTSN index isexplained on regions with hypothetical Residential Structure to show the behavior ofthe RTSN index. Further the RTSN index is applied on representative administrativeregions of the Czech Republic. The RTSN index represents a useful base forresearch of further factor influencing the level of regional Transport Services.
Keywords: Index RTSN; Regional Transport Service; Residential Structure; Urbanization